Implementation of Digital Entrepreneurs in Determining Tourism Village in Indonesia (Systematic Literature Review) - Saptarini, Atmi; Ms, Maharinisari; Ahadiat, Ayi; Bangsawan, Satria (Universitas Muhammadiyah Jakarta, 2023)
Digitalization by enterprises can improve production efficiency, processing, logistics, and adoption of new technologies so that technology integration enables the utilization of local and global economies and enterprise-level business models to be more productive and sustainable. The application of digital entrepreneurship principles is also carried out in determining tourism destinations in Indonesia. The purpose of this study is to look at a piece of writing about how to identify tourist villages through digital entrepreneurship. The source of the data was a compilation of publications that were published in reputable international scientific journals. This study's foundation is a series of inquiries, What topic is being discussed the most when it comes to tourist villages and digital entrepreneurship? The results showed that technology adoption, entrepreneurial attitude and the uniqueness of an object are factors that influence the formation of tourist villages. Technology adoption is the use of digital technology to inform the uniqueness of an object so as to encourage people to visit.